(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2024)
This work aims to develop a robotic platform coupled to radiation detectors for application in radiological accident simulation experiments. To this end, a robot was assembled on a platform on six wheels with Arduino programming, seeking movement in different degrees of freedom. The robot was controlled by remote control and viewed by a camera so the operator could follow the path taken by the robotic platform. The radiation values were seen instantly from the display of the radiation monitor/detector (RadEye). This platform model used non-destructive tests with radioactive sources in the laboratory for an environmental radiometric survey simulating a radiological accident. The results showed the command synchronization between the controller and the platform in an environment with only the presence of the background and the visualization of the instantaneous dose rate in Sv/h. However, when faced with the radiation field, there was interference in the signals and communication controlling the robot’s movements. However, due to the short exposure time to gamma rays, the electronic components did not show any damage. It can be concluded from this experience that the prototype should be improved by adding shielding to the electronic boards, which are sensitive to radioactivity. The relevance of this investigation lies in developing robotic platforms for exposure in environments that pose health risks and for the radiological protection of emergency teams in actions during radiological and nuclear accidents.